-p-1=-21

Simple and best practice solution for -p-1=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -p-1=-21 equation:


Simplifying
-1p + -1 = -21

Reorder the terms:
-1 + -1p = -21

Solving
-1 + -1p = -21

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -1p = -21 + 1

Combine like terms: -1 + 1 = 0
0 + -1p = -21 + 1
-1p = -21 + 1

Combine like terms: -21 + 1 = -20
-1p = -20

Divide each side by '-1'.
p = 20

Simplifying
p = 20

See similar equations:

| (K-p)*(r-j)= | | 3x^2-6x=x^2+x | | z+4=-4 | | m-8=-5 | | z+6=-6 | | z-7=3 | | z-7=0 | | 12+y=0 | | h/40=5 | | y-1.2=-1.3 | | 4x-3=x-15 | | a-5=66 | | x^2-6x+1=2-6x | | 5x-6=1-6x | | 7x-6=1-5x | | 6x^2+20x+12=0 | | x^2-5x+4=19-3x | | 4x+8-x+3=2x+23 | | y^2+3y+yx+3x=0 | | 10x-37=-87 | | x=8-3x | | (x-8)=4 | | (X*0.1)+X=100 | | (100*0.1)+100=X | | X*0.1=100 | | 6x+11=2x-1 | | (-3)(3+2x)+4x^2+1(1-x)=-11 | | 18x-x^2=71 | | 3x-15y=0 | | 2a+11=15 | | 36*(25+48)-16*22= | | 2x+36=6x+3 |

Equations solver categories